Impacto de las asociaciones público privadas en el desarrollo de infraestructura para la prestación del servicio público de salud : el caso del nuevo Hospital Simón Bolívar (2017)
This work develops a financial analysis of hospital infrastructure projects under the scheme of Public Private Partnerships (PPP). For this, the valuation of the Simón Bolívar Hospital will be executed in such a way that it is possible to know the present value of it and thus conclude on the profitability granted to the individuals potentially interested in the development project of the New Hospital. From the exercise it was obtained that the averages of the multiples valuation reached values that, after having calculated the appropriate discount rate (7.01%), coincided with the results of the analysis by discounted cash flow (DCF). With these results it is then possible to affirm that the asset is profitable and the development of the PPP project generates value. Also, in addition of a correctly executed exercise, it was possible to show a relevant problem for the development of the national economy.--Tomado del Formato de Documento de Grado.